2018
DOI: 10.1155/2018/6590710
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mass of a Fetus Incidentally Found during Second Trimester: Ultrasound Survey and Postnatal Prognosis of the Baby

Abstract: Ultrasound (USG) and magnetic resonance imaging (MRI) can be used to detect and evaluate the face and neck tumors during the in-utero period. We reported and discussed an oral mass which was diagnosed incidentally at mid-trimester exam and managed successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[1] The MRI done before delivery showed no evidence of fetal airway obstruction and/or intracranial extension or central nervous system-related anomalies. [10]…”
Section: Discussionmentioning
confidence: 99%
“…[1] The MRI done before delivery showed no evidence of fetal airway obstruction and/or intracranial extension or central nervous system-related anomalies. [10]…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of a mass in the oral cavity should include teratoma, epulis, mucosal retention cyst, duplication foregut cysts, dermoid cyst, and other benign or malignant soft-tissue masses. [4][5][6][7][8][9][10] Some studies in the literature have demonstrated that the most common types of fetal oral solid masses were teratoma and epulis. 12 In our series, we reported 6 cases of fetal oral masses, including LM in 2 fetuses and mucosal retention cyst, mature teratoma, immature teratoma, and cranial meningocele in 1 fetus, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest diagnosis of fetal oral mass in our study was at 13 weeks of gestation; however, the vast majority of lesions were observed in the second and third trimesters, which suggests that the tumor can develop later in pregnancy. The differential diagnosis of a mass in the oral cavity should include teratoma, epulis, mucosal retention cyst, duplication foregut cysts, dermoid cyst, and other benign or malignant soft‐tissue masses 4–10 . Some studies in the literature have demonstrated that the most common types of fetal oral solid masses were teratoma and epulis 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations